English Writing Activities at Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Prov. Sulawesi Selatan - Andi Dhea; Fatimah Hidayahni; La Sunra La Sunra (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aims to identify employee activities in working out the English document. This study used a qualitative method with descriptive design and conducted at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Prov. Sulawesi Selatan. The data of this research were collected through interviews and documents. The data were analyzed in four steps: data collection, data condensation, data display, drawing, and verifying conclusion. The results revealed that English working activities have the basis of writing components that are conceptualizing and writing the content of the documents, arranging and confirming the idea of organization, looking for the meaning and matching appropriate vocabulary, correcting and re-checking English grammar, and correcting the document' mechanism. Based on these results, the English working activities in the office are dominant in a writing activity. The biggest challenge faced by the employee is that there are a lot of Economic topics and terms unfamiliar to the employee and the use of structure. The suggestion is that the employee emphasizes self-study about writing and its components and learns more about the investment field. Moreover, the office provided English training for employees to increase employees' skills and motivation in working.Keywords: English in the workplace, Writing component, Difficulty in writing